Derazantinib: an investigational drug for the treatment of cholangiocarcinoma. (2nd November 2021) - Braun, Stephan; McSheehy, Paul; Litherland, Karine; McKernan, Phil; Forster-Gross, Nicole; Bachmann, Felix; El-Shemerly, Mahmoud; Dimova-Dobreva, Miryana; Polyakova, Inessa; Häckl, Manuel; Zhou, Ping; Lane, Heidi; et al.
ABSTRACT: Introduction: This review evaluates the clinical role of fibroblast growth factor receptor 2 (FGFR2) inhibition with derazantinib in patients with intrahepatic cholangiocarcinoma (iCCA) harboring actionable oncogenic FGFR2 fusions/rearrangements, mutations and amplifications. FGFR inhibitors such as derazantinib are currently being evaluated to address the unmet medical need of patients with previously treated, locally advanced or metastatic iCCA harboring such genetic aberrations. Areas covered: We summarize the pharmacokinetics, and the emerging safety and efficacy data of the investigational FGFR inhibitor derazantinib. We discuss the future directions of this novel therapeutic agent for iCCA. Expert Opinion: Derazantinib is a potent FGFR1‒3 kinase inhibitor which also has activity against colony stimulating factor-1‒receptor (CSF1R) and vascular endothelial growfth factor receptor‒2 (VEGFR2), suggesting a potentially differentiated role in the treatment of patients with iCCA. Derazantinib has shown clinically meaningful efficacy with durable objective responses, supporting the therapeutic potential of derazantinib in previously treated patients with iCCA harboring FGFR2 fusions/rearrangements, mutations and amplifications. The clinical safety profile of derazantinib was well manageable and compared favorably to the FGFR inhibitor class, particularly with a low incidence of drug-related hand-foot syndrome, stomatitis, retinal and nail toxicity. These findings support the need for increased molecular profiling of cholangiocarcinoma patients.